Antioxidant activities and total phenolic content of Malaysian herbs and their effect as active packaging film in meat patties - Wan Amnin, Wan Yahaya; Alyaa Syahierra, Ghazali; Khadijah Husna, Abd. Hamid; Neenasha Bebe, Mohd Nor; Nurul Aini, Mohd Azman (Universiti Malaysia Pahang, 2019)
Active packaging incorporated with natural extracts is a promising technology to extend shelf life of perishable food. Therefore, this study aims to produce the bioactive edible film from semi refined carrageenan (SRC) plasticized with glycerol (G) and incorporated with natural extract to improve lipid oxidative stability and storage quality of meat patties. Evaluation of five Malaysia herbs (Cosmos caudate; CC, Piper sarmentosum; PS, Persicaria minor; PM, Centella asiatica; CA and Syzygium polyanthum; SP) were analysed for their phenolic content and antioxidant activities and total phenolic content using Folin-Ciocaltea method, and the antioxidant activities of plants were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, trolox equivalent antioxidant capacity (TEAC) and oxygen radical absorbance capacity (ORAC). PM extract demonstrated highest total phenolic content (1.629 mgGAE/Lsample) and antioxidant activities value in TEAC (27.166 mg TE/ L sample), DPPH (719.89 mg eq. trolox/L sample ) and ORAC (5.81 mg TE/ L sample). Thus, PM extract was selected to be incorporated into active packaging film with concentration of 0.4,1.5 and 2.0% in 2% SRC and 0.9% G (w/w) film formulation. The developed films were wrapped with meat patties under refrigerated condition (4±2℃) and monitored for 14 days storage period. Film wrapped with 2% (w/w) PM exhibited significantly lower lipid deterioration rate analyzed by TBARS method (p<0.05) and low changes of % metmyoglobin value that indicates the minimum development of brown color (p<0.05). Hence, the active packaging edible films incorporating PM demonstrated potential as a packaging material to improve food safety and quality of the meat.